The Effect of Awareness of Tax Laws, Understanding of Tax Laws and Tax Compliance Behaviour on Supply Chain Management - Moenek, Reydonnyzar (International Journal of Supply Chain Management, 2020)
Abstract- The objective of this study is to explore the role of tax education in supply chain management (SCM) among Indonesian supply chain companies. To approach this objective, the study examined the effect of awareness of tax laws and understanding of tax laws on tax compliance behaviour. After that, the collective role of awareness of tax laws, understanding of tax laws and tax compliance behaviour was examined on SCM. Managerial employees were selected as the respondents to collect the primary data. Total seven hypotheses were established concerning the relationship of awareness of tax laws, understanding of tax laws, tax compliance behaviour and SCM to achieve the objective. A total number of two hundred (200) survey questionnaires were distributed among the respondents. All the hypotheses were supported by the current study. It was found that tax education has a significant relationship with SCM. Awareness of tax laws and understanding of tax laws supports SCM practise among Indonesian supply chain firms. Tax compliance behaviour enhances the positive effect of awareness of tax laws and understanding of tax laws on SCM. Therefore, tax compliance behaviour is a mediating variable to enhances the effect of tax education on SCM.